2022
DOI: 10.3389/fbuil.2022.1006365
|View full text |Cite
|
Sign up to set email alerts
|

High potential of small-room acoustic modeling with 3D time-domain finite element method

Abstract: Applicability of wave-based acoustics simulation methods in the time domain has increased markedly for performing room-acoustics simulation. They can incorporate sound absorber effects appropriately with a local-reaction frequency-dependent impedance boundary condition and an extended-reaction model. However, their accuracy, efficiency and practicality against a standard frequency-domain solver in 3D room acoustics simulation are still not known well. This paper describes a performance examination of a recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Okuzono et al [90] implemented a frequency-dependent absorbing boundary using the ADE method and found good agreement between FEM solutions in the time domain and the frequency domain. Okuzono and Yoshida [137] modeled the frequency dependence of both LR and ER materials in the time domain.…”
Section: Frequency-dependent Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okuzono et al [90] implemented a frequency-dependent absorbing boundary using the ADE method and found good agreement between FEM solutions in the time domain and the frequency domain. Okuzono and Yoshida [137] modeled the frequency dependence of both LR and ER materials in the time domain.…”
Section: Frequency-dependent Materialsmentioning
confidence: 99%
“…The coupled model was used to simulate the measurement of impedance in an impedance tube, and good agreement with analytical data was found. Okuzono & Yoshida [137] considered the FEM in the time domain for small room acoustics. They modeled frequency-dependent LR and ER sound absorbers, and simulated impulse responses up to 6 kHz.…”
Section: Extended Reaction Materialsmentioning
confidence: 99%
“…Wave-based room acoustics simulation using the finite element method (FEM) attracts intense interest because of its high flexibility for boundary shape modeling. Recently, by virtue of the development of highly efficient solvers with a sound-absorbing boundary considering the frequency-dependent complex-valued surface impedance of soundabsorbing materials, it is becoming possible to apply timedomain finite element method (TD-FEM)-based numerical solvers to the broadband acoustic modeling of realistic rooms [1][2][3][4][5][6][7]. However, for more precise simulations of room acoustics, it is crucially important to use extendedreaction (ER) sound-absorbing models able to incorporate both the frequency and incident-angle dependences of absorbing materials.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, thin materials such as permeable membranes and microperforated panels (MPPs) have been modeled with interior impedance boundary conditions [15][16][17]. Nevertheless, recent work [6] has demonstrated that TD-FEM has benefits for computational times for large-scale problems such as real-sized 3D room acoustics simulation. Therefore, developing a TD-ER model for TD-FEM to realize high-efficiency wave-based room acoustics simulation is an attractive topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation